Transformation of adenocarcinoma into small cell lung cancer as one of the mechanisms of acquired resistance to anti-EGFR tyrosine kinase inhibitors - O. O. Kovalov; O. P. Tolok; K. O. Kovalov (Zaporozhye State Medical University, 2024)
Transformation of adenocarcinoma into small cell lung cancer (SCLC) is a rare and unique biological property of a cancer cell that is responsible for the mechanism of acquired resistance to EGFR tyrosine kinase inhibitors. There are very few clinical observations of phenotypic cellular transformation during metastatic progression of lung cancer in the literature. The aim of the work is to demonstrate clinical observation of phenotypic transformation of metastatic EGFR-mutated adenocarcinoma into small cell lung cancer with neuroendocrine differentiation during therapy with tyrosine kinase inhibitors. Case report. Due to the rarity of this biological phenomenon, we describe our own observation of the transformation of EGFR-mutated metastatic adenocarcinoma into DCLC with neuroendocrine differentiation, which occurred in a 42-year-old woman during treatment with gefitinib. Conclusions. Transformation and changes in cell phenotype during tyrosine kinase inhibitor therapy were the cause of resistance and failure of further treatment with osimertinib in the second line. It was concluded that it is necessary to consider this mechanism of resistance in clinical practice and to perform repeat biopsies during metastatic progression in patients with EGFR-mutated lung adenocarcinoma.